2019
DOI: 10.1101/559310
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

RASSF1A is required for the maintenance of nuclear actin levels

Abstract: Nuclear actin participates in many essential cellular processes including gene transcription, chromatin remodelling and mRNA processing. Actin shuttles into and out the nucleus through the action of dedicated transport receptors importin‐9 and exportin‐6, but how this transport is regulated remains unclear. Here, we show that RASSF1A is a novel regulator of actin nucleocytoplasmic trafficking and is required for the active maintenance of nuclear actin levels through supporting binding of exportin‐6 (XPO6) to R… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 60 publications
2
15
0
Order By: Relevance
“…Moreover, another study suggests the link between RASSF1A and endosomal trafficking through interaction with tumor necrosis factor receptor 1, and states that TNF-R1 internalization is probably dependent on a stable microtubular network influenced by RASSF1A 16 . In addition, a recent report uncovered a new role for endogenous RASSF1A as a regulator of actin nucleocytoplasmic trafficking by corroborating binding of transport receptor exportin-6 to RAN GTPase 89 . Thereby, given the ability of dysregulated vesicle trafficking to promote cancer cell invasion and metastasis 90 , and exosomes to create a pre-metastatic niche 91,92 , their malfunction could contribute to cancer progression of RASSF1A-depleted cells.…”
Section: The Role Of Rassf1a’s Scaffold Activity In Prevention Of Carmentioning
confidence: 91%
“…Moreover, another study suggests the link between RASSF1A and endosomal trafficking through interaction with tumor necrosis factor receptor 1, and states that TNF-R1 internalization is probably dependent on a stable microtubular network influenced by RASSF1A 16 . In addition, a recent report uncovered a new role for endogenous RASSF1A as a regulator of actin nucleocytoplasmic trafficking by corroborating binding of transport receptor exportin-6 to RAN GTPase 89 . Thereby, given the ability of dysregulated vesicle trafficking to promote cancer cell invasion and metastasis 90 , and exosomes to create a pre-metastatic niche 91,92 , their malfunction could contribute to cancer progression of RASSF1A-depleted cells.…”
Section: The Role Of Rassf1a’s Scaffold Activity In Prevention Of Carmentioning
confidence: 91%
“…Nanaomycin A demethylated the DNA and reactivated the transcription and expression of the gene RASSF1A (ras association domain family 1 isoform A). RASSF1A is a TSG frequently silenced by promoter hypermethylation in cancer [ 101 ]. Kuck et al noted that in lung cancer cells, the promoter region of RASSF1A was sequenced by bisulfite sequence, which confirmed that RASSF1A promoter was highly methylated in A549 cells [ 40 ].…”
Section: Targeting Dnmtsmentioning
confidence: 99%
“…A very recent study demonstrated that Ras association domain family isoform 1A (RASSF1A), which is a tumor suppressor frequently silenced in solid cancer supports the binding of Exportin-6 to Ran GTPase, and thus contributes to nucleo-cytoplasmic shuttling of actin. Interestingly, this pathway is aberrant in cancer cells, which results in increased nuclear actin levels and consequently to decreased expression of MRTF-A-SRF target genes [67]. Still another factor regulating MRTF-A/SRF activity is the F-actin binding protein filamin A, which has been shown to interact with MRTF-A, positively regulating SRF activation and thereby postulated to link nuclear actin polymerization to the MRTF-A/SRF transcription complex [68].…”
Section: Dynamic Nuclear Actin In Gene Expressionmentioning
confidence: 99%